Rearrangement and transcription of a T-cell receptor beta-chain gene in different T-cell subsets. - Hedrick, S M (1985)
The functionally defined sets of T lymphocytes--helper T cells, cytotoxic T cells, and suppressor T cells--were examined for the possible involvement of a recently identified T-cell receptor beta gene locus in receptor formation. Since gene rearrangements are required for functional gene expression, cloned T-cell lines from each of the groups were surveyed for the expression of unique gene rearrangements. In addition, cell lines that showed gene rearrangements were further tested for the expression of the mature 1.2- to 1.3-kilobase mRNA transcribed from a productive gene rearrangement. The results of such experiments show that helper and cytotoxic T cells may use a common beta chain of the receptor, whereas suppressor cells do so rarely, if at all.